UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI KEMAMPUAN KOMUNIKASI INTERPERSONAL GURU - Sidik, Zafar; Sobandi, A (Universitas Pendidikan Indonesia, 2018)
The problem in this research was students? learning motivation which is not optimal. It is characterized by a recapitulation of the students? attendance that is not on maximum category and acquisition of learning outcomes of students which have not reached the Minimum Mastery Criteria in school. This article aims to show the results of research on the effect of interpersonal communication skill of teacher towards students? learning motivation in grade XI of office administration class in one of the Private Vocational School in Cimahi. The method used in this research was explanatory survey, with respondents as many as 57 students. The results of data analysis showed that the students' learning motivation is in the medium category and teachers' interpersonal communication skills are in fairly effective category. However, teachers' interpersonal communication skills has a positive and significant impact on students? learning motivation. In order to increase students' learning motivation, it is needed to improve effectiveness of teachers? interpersonal communication.ABSTRAKPermasalahan dalam penelitian ini adalah belum optimalnya motivasi belajar siswa. Hal ini ditandai dengan rekapitulasi kehadiran siswa yang belum maksimal dan perolehan hasil belajar siswa yang belum mencapai Kriteria Ketuntasan Minimum (KKM) di sekolah. Artikel ini bertujuan untuk memaparkan hasil penelitian tentang pengaruh kemampuan komunikasi interpersonal guru terhadap motivasi belajar siswa kelas XI Administrasi Perkantoran di salah satu Sekolah Menengah Kejuruan (SMK) swasta di Cimahi. Metode yang digunakan dalam penelitian ini adalah metode survey eksplanatory, dengan responden sebanyak 57 orang siswa. Hasil analisis data menunjukkan bahwa motivasi belajar siswa berada pada kategori sedang dan kemampuan komunikasi interpersonal guru berada pada kategori cukup efektif. Namun demikian, komunikasi interpersonal guru memiliki pengaruh yang positif dan signifikan terhadap motivasi belajar siswa. Untuk meningkatkan motivasi belajar siswa, maka perlu ditingkatkan efektivitas komunikasi interpersonal guru.